Legal evidence theory - Accatino, Daniela (Revus (Ljubljana), 2020)
This paper focuses on the rationalist theory of evidence and identifies a set of two basic theses and their underlying philosophical assumptions shared by the Anglo-American and the Latin versions of rationalism: the thesis of the pursuit of truth as the preferential aim of legal evidence; the thesis of evidentiary justification as a special case of general epistemic justification; the assumption of the notion of truth as correspondence; the assumption of ontological and epistemological differentiation of rationalism from both skepticism and naive cognitivism. The author sustains that these theses and assumptions are imprecise in important aspects and that this is what allows the adoption of the rationalist conception to function as the common frame for current debates in legal theory of evidence, a frame that closes some discussions (namely, those concerning the notion of truth) and opens others (those regarding the degree of specificity of legal evidentiary justification and the appropriate way to allocate the risk of error).
Keywords: dokazno pravo; dokazno utemeljevanje; evidence law; evidentiary justification; racionalistično izročilo; rationalist tradition; resnica; risk of error; truth; tveganje napake